INFLUENCE OF BALL RESIN TO SHOT ACCURACY IN HANDBALL - Siniša Karišik,; Danijel Božić,; Tijana Tirić, (Sport Scientific And Practical Aspects, 2025)
Opinions of handball experts differ in terms of importance of individual elements of handball technique, but they are all in agreement that shot is relevant and important factor. Shot velocity and accuracy gain importance in terms of score outcome of the game. We may draw a conclusion that they are two basic factors and that they are extremely significant for shot efficiency. In this paper, research will be aimed answering whether and to what extent ball resin influences shot accuracy. The sample consists of 20 male handball players, members of handball clubs which play in Serbian Super league aged 17 to 36, systematically training for at least two years without longer brakes. For the purpose of accuracy assessment the participants shot equilateral triangles positioned between the goal posts in upper and lower corners. Shot was performed with size 3 handball with and without resin as follows: jump shot from 9-meter distance (SMP9M), 7-meter throw from standing position (SMP7M) and shots by positions (SMPP). For the purpose of determining the statistical significance all the data was processed at univariant level, the descriptive parameters were calculated and after that the Student’s t-test for paired samples was applied at the multi-variant level and relevant parameters were defined. Results of the Student’s t-test for paired sampled provided confirmation for identification of statistically significant differences between mean values: (SMP9ML – SMP9MBL .001, SMP7ML – SMP7MBL .006 and SMPPL –SMPPBL .024) at the statistical significance level p < .05.